On the Discoursal Function of Some Special Textual Strategies in Poetic Texts: Implications for Literary Translation - Lotfipour-Saedi, Kazem (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractThe special literary patterns have already been studied under the general category of literary textual strategies where it has been argued how these textual strategies would set the special literary processes in motion in the cognitive system of the receiver leading to the formation of a special literary meaning, i.e. the literary effect (cf. Lotfipour-Saedi 1992a). The present paper will examine two types of literary textual strategies and the way they function in the activation of the special literary discourse process.